PENGARUH METODE SAMBUNG AYAT AL-QURÁN JUZ 30 DALAM MENINGKATKAN MOTIVASI MENGHAFAL SISWA SD KARTIKA XII-1 - wahyuningrum, zulfa indra; Mawardi, Imam (AL-QALAM: JURNAL ILMU KEPENDIDIKAN, 2022)
Learning the Qur'an at a young age is very important because religious learning through the ability to read the Qur'an is a foundation that must be formed from an early age. Being able to read the Qur'an is one of the skills that is currently needed. As one of the media to foster the character of akhlaqul karimah in the independent curriculum, namely the dimensions of faith, piety to God Almighty, and noble character. This research was made to find out how the influence of the verse connecting method in increasing motivation to memorize the Al-Qurán Juz 30. The data collected through observation and documentation and analyzed qualitatively. In this study, data were obtained that the verse connecting method was able to increase motivation to memorize Al-Qurán short letters (Juz 30) of SD Kartika XII-1 students. This study proves that the verse connecting method can increase the motivation to memorize the Al-Qurán juz 30 in SD Kartika XII-1 students. Keywords: Paragraph Connection Method, Motivation, Memorizing